Gd-DTPA-enhanced MR imaging of the brain in patients with meningitis: comparison with CT. - Chang, K H; Han, M H; Roh, J K; Kim, I O; Han, M C; Kim, C W (American Journal of Neuroradiology, 1990)
Plain and Gd-DTPA-enhanced MR images of the brain were obtained in 18 consecutive patients with meningitis (eight with tuberculous, five with bacterial, three with viral, and two with fungal infections); the MR images were compared with CT scans. MR images were obtained on a 2.0-T superconducting unit with both T1- and T2-weighted pulse sequences before injection and with a T1-weighted sequence after injection of Gd-DTPA (0.1 mmol/kg) in all patients. In tuberculous meningitis, MR imaging depicted ischemia/infarct, hemorrhagic infarct of basal ganglia, meningeal enhancement at either basal cistern or convexity surface of brain, and associated small granulomas in a few more patients than CT did. In bacterial meningitis, primary foci of extracranial inflammation (i.e., mastoid, paranasal sinuses) and adjacent intracranial lesions including localized dural inflammation, subdural fluid collection, and/or brain parenchymal lesions were demonstrated much better on MR than on CT. Otherwise, MR images generally matched the CT scan. Although the plain MR images, both T1- and T2-weighted, were the most sensitive in delineating ischemia/infarct, hemorrhage, and edema, they were not as specific as Gd-DTPA-enhanced T1-weighted images and postcontrast CT scans in defining the active inflammatory process of the meninges and focal lesions precisely. We conclude that if Gd-DTPA is used, MR imaging appears to be superior to CT in the evaluation of patients with suspected meningitis. Precontrast MR is needed to delineate ischemia/infarct, edema, and subacute hemorrhage.